The development of microbiological methods for drug analysis - O. V. Gunar; N. G. Sakhno; E. S. Novik; G. M. Bulgakova; L. V. Kolosova; I. A. Buylova; M. V. Roshchina (Регуляторные исследования и экспертиза лекарственных средств)
The article presents the review of the national regulatory documents on drug testing for microbiological characteristics, such as «Sterility», «Microbiological Purity» etc. It discusses the history of the establishment of characteristics and the elaboration of the related general pharmacopoeia monographs, as well as prospects for the development of methods in connection with the publication of the Russian State Pharmacopoeia XIII edition. There is a clear trend towards harmonization with the leading world pharmacopoeias, but the Russian State Pharmacopoeia maintains the individual characteristics of drug quality analysis in terms of microbiological characteristics, including the introduction of new technologies, process automation and taking into account the special features of individual drug groups.